“Auto-combed hair”. A clinicopathological study of a possibly “de novo” hair defect. - Shelleh, H.H.; Dawood, S. (European Journal of Pediatric Dermatology, 2007)
We report two brothers who displayed a bizarre type of congenital hypotrichosis, trans-mitted in four generations. In adult patients of these families, the hairs of the eyebrows, eyelashes, beard, moustache, armpits, and pubic region were very scarce and dystrophic. Vice versa, the scalp hair was adequate in quantity and length, but was dark black, coarse, tidy and shining as if "auto combed". All nails were fragile and white, with lamellar desquamation. Keratosis pilaris existed on the face and limbs. Teeth, sweat glands and the rest of systemic examination were normal. The microscopic and ultra-structural study of the skin and hair from axillary region only showed the scarcity of hair follicle units in the skin. This hair and nail defect followed an autosomal dominant trait in the involved pedigrees. Literature review did not reveal similar cases, which should included within the subgroup 1-3 of Pinheiro and Freire-Maia classification.